Friction material composition and related friction element

By introducing carbonaceous materials with different particle size distributions into the friction material composition, the porosity and component ratio of the friction material are optimized, and the shortcomings of existing friction materials in low frequency noise, friction stability and particle emission are solved, and the reduction of existing friction materials is achieved. More efficient braking performance and lower environmental impact.

CN119404023APending Publication Date: 2025-02-07ITT ITAL SRL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047892.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-20
Filing Date
2023-06-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing friction material compositions have shortcomings in reducing low frequency noise and friction stability, and are difficult to take into account both braking performance and comfort.

Method used

A asbestos-free friction material composition is developed, which comprises a carbonaceous material with particle size distributions greater than 10 μm and less than 10 μm, to improve friction stability and reduce particle emissions by optimizing the porosity and component ratio of the friction material. .

Benefits of technology

The friction material composition significantly reduces peristaltic flutter noise and particle emissions, improves friction stability and braking performance, and reduces material wear and heat accumulation in braking applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404023A_ABST
    Figure CN119404023A_ABST
Patent Text Reader

Abstract

An asbestos-free friction material composition and a related brake pad for a vehicle, in particular for an electric vehicle, having improved friction stability, reduced tendency to creep chatter noise and lower particle emissions wherein the composition comprises: at least one filler; at least a fibrous material; at least one binder; at least one lubricant; at least one or more abrasives; at least a first carbonaceous material having a particle size distribution such that D50 is greater than 10 [mu] m; and at least a second carbonaceous material having a particle size distribution such that it has a D50 of less than 10 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This patent application claims the priority of Italian Patent Application No. 102022000013012 filed on June 20, 2022, the entire disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a friction material composition which is particularly suitable for use in the manufacture of a friction layer / shoe for a friction element, such as a brake element to be incorporated, for example, in a vehicle brake system.

[0004] The present invention also relates to related friction elements (such as brake pads or brake shoes for vehicles) made with the friction material composition, and is particularly but not exclusively suitable for electric vehicles.

[0005] The friction material composition of the invention is free of asbestos, is of the so-called NAO (“Non Asbestos Organic”) type, and is particularly, but not exclusively, free of copper. Background Art

[0006] With the rapid development of the modern transportation industry, the number of electric vehicles is increasing day by day.

[0007] Replacing internal combustion engines with electric engines results in much quieter vehicles. This has led to a higher concern for noises generated by other automotive components, such as those generated by brake pads embedded in the braking system. Therefore, brake pads for electric vehicles require improved NVH (Noise, Vibration, Harshness) standards for driving comfort, while maintaining and in some cases improving braking performance in terms of friction stability, static friction and corrosion cleanliness.

[0008] At the same time, future mobility trends pay special attention to environmental and health hazards, aiming to reduce emissions of particulate matter (PM10 and PM2.5), for example, generated by braking systems.

[0009] With regard to the operating noise of the braking system, it is known that this phenomenon has a complex and multifactorial origin and depends both on the driving vibrations of the vehicle associated with the unavoidable assembly clearances between the braking elements (e.g. brake pads and brake shoes) and the corresponding supports during the start-up of the braking system, and on contact phenomena occurring between the sliding parts of the braking elements and the supports.

[0010] This contact phenomenon is known as "creep groan" and it generates an annoying high-intensity and low-frequency noise at very low vehicle speeds. It is a typical example of self-excited brake vibrations caused by the so-called "stick-slip" effect, i.e. by the alternating adhesion or sticking of the brake pad on the brake disc and subsequent sliding during the braking process, and as a result, the friction coefficient constantly changes between static (sticking phase) and dynamic (slipping phase) values.

[0011] With regard to modern vehicles, such as electric vehicles, there is a strongly felt need to eliminate or at least reduce low frequency noise in a simple and, above all, economical manner.

[0012] In fact, as far as electric vehicles are concerned, they are much quieter than their internal combustion engine counterparts. In particular, unlike engine-driven vehicles, electric vehicles start moving quietly due to the electric motor. Therefore, drivers and passengers are more likely to feel the noise as described above and may make them feel uncomfortable. In addition, these types of noise may affect the living environment of residents and may become a new source of noise pollution in cities.

[0013] Various solutions are known in the art that attempt to reduce this phenomenon, but they do not completely solve the problem or present other disadvantages.

[0014] EP0959262 discloses a disc brake pad capable of reducing creeping vibration using a composition comprising a fiber substrate other than asbestos, a binder and a friction modifier, wherein the binder is composed entirely or partially of a modified silicone resin, and wherein, in combination, the friction material composition comprises 0.5 to 20 volume % of zeolite as part of the friction modifier, and the modified silicone resin is contained in the friction material composition in an amount of 3 to 30 volume % of the total composition. The modified silicone resin is obtained by reacting oil or silicone rubber with a novolac type phenolic resin. This results in a material that is expensive and difficult to produce.

[0015] On the other hand, WO2019120648 discloses a hybrid friction lining material and a brake pad made thereof, in which an attempt is made to combine the positive properties of a low steel friction lining material (so-called low steel (LS) friction lining or friction lining material) and an asbestos-free organic friction lining material. In a preferred embodiment, such a mixed friction material comprises: 15% to 22% by weight (by weight), in particular 17% to 20% by weight of at least one binder; 5% to 11% by weight of organic fibers or a mixture of organic fibers; 1% to 20% by weight, in particular 8% to 14% by weight of at least one other organic compound; zero or 8% to 16% by weight of inorganic fibers or a mixture of inorganic fibers; 10% to 40% by weight of at least one inorganic oxide; 6% to 12% by weight of at least one inorganic silicate; 13% to 15% by weight of sulfur or at least one inorganic sulfur compound; 10% to 16% by weight of carbon or at least one material essentially consisting of carbon, in particular selected from natural graphite, synthetic graphite, petroleum coke, dried petroleum coke, carbon black and any mixture thereof; 1% to 1.5% by weight of at least one filler selected from the group of inorganic hydroxides, in particular calcium hydroxide; and zero to a maximum of 1% by weight of at least one metal, in particular iron or iron alloys.

[0016] However, such hybrid materials produce a compromise behavior in terms of braking performance and comfort, which may not be optimal or desirable for many applications.

[0017] CN106015399 discloses a friction material for electric vehicle brake pads. The friction material comprises by weight: 25 to 30 parts of carbon fiber, 10 to 15 parts of aramid fiber, 40 to 50 parts of nitrile rubber, 20 to 30 parts of styrene-butadiene rubber, 10 to 20 parts of carbon black, 5 to 12 parts of composite mineral fiber, 1 to 3 parts of sulfur, 1 to 4 parts of vermiculite, 2 to 7 parts of epoxy resin, 6 to 15 parts of barium sulfate, 3 to 8 parts of graphite, 0.5 to 1 parts of accelerator, 2 to 4 parts of stabilizer, 1 to 2 parts of water. However, brake pads containing such friction material do not show any shortcomings in terms of noise and particle emission reduction and friction stability improvement. Summary of the invention

[0018] The object of the present invention is to develop new asbestos-free friction material compositions which are able to overcome the disadvantages of the prior art and which concomitantly exhibit improved braking performance in terms of low-frequency noise and friction stability and reduced particle emissions. In particular, the presently disclosed subject matter aims to provide asbestos-free friction material compositions which combine improved creeping chatter and friction stability by reducing the tendency of the friction shoe to adhere to the surface of the friction partner cooperating therewith, and reduced particle emissions by reducing material wear and optimizing heat dissipation.

[0019] Accordingly, the present invention relates to a friction material composition as defined in the appended claims.

[0020] Another object of the present invention is to provide a friction element, in particular a brake pad or a brake shoe, comprising the friction material composition.

[0021] Further features and advantages of the disclosed subject matter, whether explicitly mentioned or not, will become apparent in view of the disclosure provided below.

[0022] The present disclosure therefore relates to friction material compositions belonging to the class of friction materials known as NAO (Non-Asbestos Organic), which aim to obtain improved stick-slip behavior with respect to the known NAO friction compositions in order to benefit the creep shudder phenomenon and friction stability, as well as to reduce particle emissions.

[0023] In fact, unlike the known NAO friction composition, the disclosed friction material composition comprises in combination the following: 50 The particle size distribution of at least a first carbonaceous material and at least a second carbonaceous material.

[0024] Due to the combination of at least a first carbonaceous material and at least a second carbonaceous material, the disclosed friction material composition results in both reduced stick-slip phenomena (which in turn positively affects both creep shudder noise and friction stability) and reduced particle emissions. Specifically, the friction element comprising the disclosed friction material composition renders the brake system less prone to stick-slip behavior, primarily due to the optimal porosity of the friction material, which improves adhesion between the friction element and the brake disc, and which reduces the negative effect of humidity on the coefficient of friction.

[0025] At the same time, reduced particulate emissions result from the synergistic effect of the first carbonaceous material, which reduces friction between the brake disc and the friction element for the benefit of friction element durability, and the second carbonaceous material, which dissipates heat generated during brake application rather than allowing the heat to accumulate in the friction element, thereby damaging the binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Further characteristics and advantages of the invention will become apparent from the following description, based on practical and comparative non-limiting examples and with reference to the accompanying drawings, in which:

[0027] - Figure 1 Presented are the results of wear tests conducted on friction elements made from two friction material compositions, one according to the present invention and the other made from a comparative friction material composition;

[0028] - Figure 2 A report showing the results obtained from AK-Master testing of friction elements made from comparative friction material compositions;

[0029] - Figure 3 A report showing the results obtained from the AK-Master test of friction elements made from the friction material composition according to the present invention;

[0030] - Figure 4 shows the results of creep flutter tests of two friction elements made of friction material compositions according to two different embodiments of the present invention and one friction element made of a comparative friction material composition;

[0031] - Figure 5 Porosity characterizations of two friction elements made of friction material compositions according to two different embodiments of the present invention and one friction element made of a comparative friction material composition are shown. DETAILED DESCRIPTION

[0032] In more detail, the disclosed asbestos-free friction material composition comprises at least one filler, at least one fiber material, at least one binder, at least one lubricant, and at least one filler having a D of greater than 10 μm and less than 10 μm, respectively. 50 At least a first carbonaceous material and at least a second carbonaceous material having a particle size distribution, and at least one or more abrasives.

[0033] Here and hereinafter, “particle size distribution D 50 ” corresponds to the value of the particle diameter at 50% in the cumulative distribution.

[0034] Preferably, the D 50 The at least first carbonaceous material is present in the disclosed composition in an amount ranging from 2 wt % to 6 wt % based on the total weight of the friction material composition.

[0035] Preferably, the D 50 The at least second carbonaceous material is present in the disclosed composition in an amount ranging from 1 wt % to 4 wt % based on the total weight of the friction material composition. Most preferably, the at least second carbonaceous component is present in an amount of 2 wt %.

[0036] The content ratio of the first carbonaceous material to the second carbonaceous material may range from 1:1 to 6:1, and preferably from 2:1 to 3:1, by weight.

[0037] With D greater than 10 μm 50 The first carbonaceous material may be selected from graphite, petroleum coke, dried petroleum coke, carbon black and any mixture thereof. Preferably, the carbonaceous material has a D of greater than 10 μm. 50 The first carbonaceous material is graphite.

[0038] With a D less than 10 μm 50 The second carbonaceous material is selected from fillers including carbon black.

[0039] In addition to the at least first carbonaceous material and the at least second carbonaceous material, the other components of the disclosed friction material composition mentioned above may be components for friction materials that have been known in the art.

[0040] In particular, the at least one fiber material may be selected from inorganic fibers, organic fibers, metal fibers, and any combination thereof.

[0041] Preferably, the at least one fiber material comprises organic fibers selected from the group consisting of polyacrylic fibers, polyaramid fibers, aramid fibers, cellulosic fibers, and mixtures thereof.

[0042] Organic fibers may preferably, but not exclusively, be included in the friction material composition of the present disclosure as part of the organic binder, as they may have the primary purpose of enhancing the strength of the brake pad / shoe under operating conditions of the friction material composition of the present disclosure.

[0043] The at least one binder is preferably an organic binder and may be selected from phenolic resins, epoxy resins, silicone resins, modified phenolic resins, melamine resins, polyamide resins and mixtures thereof.

[0044] The at least one lubricant may preferably, but not exclusively, consist of a sulfide-based lubricant selected from the group comprising metal sulfides of Sn, Zn, Fe, Mo and mixtures thereof.

[0045] Many materials can be used as organic or inorganic fillers. Preferably, at least one filler is an inorganic filler selected from the group consisting of mineral fibers, glass fibers, rock wool, layered silicates (mica, vermiculite, talc, etc.), titanates, inorganic hydroxides of calcium, magnesium, potassium, and any mixture thereof.

[0046] The at least one or more abrasive materials include at least one soft abrasive material having a Mohs hardness lower than 7 and at least one hard abrasive material having a Mohs hardness higher than 7.

[0047] The content ratio of the soft abrasive to the hard abrasive by weight ranges from 1:1 to 4:1, and may preferably be 2:1.

[0048] The hard abrasive (ie having a Mohs hardness above 7) preferably, but not exclusively, has a slightly rounded shape and is preferably, but not exclusively, selected from zirconium oxide, aluminum oxide, corundum, silicon carbide, tungsten carbide, zirconium carbide, zirconium silicate, boron nitride and any mixtures thereof.

[0049] The soft abrasive (ie having a Mohs hardness below 7) may preferably, but not exclusively, be selected from magnesium oxide, chromite, magnetite, hematite, quartz, zinc oxide, tin oxide, barium sulfate, silicates, fluorides and any mixtures thereof.

[0050] According to a preferred embodiment of the present invention, the disclosed friction composition is free of copper.

[0051] Here and hereinafter, the expression “free of copper” is to be understood as implying that the content of copper and / or copper-containing materials, such as copper alloys, is 0.5 wt.-% or below.

[0052] When present in the disclosed friction material composition, the at least one metal or mixture of metals does not consist of copper and / or any copper alloy, but is selected from iron, steel, stainless steel, tin, zinc, and any alloys thereof in powder or fiber form.

[0053] Furthermore, the disclosed friction material composition may include an organic additive selected from polytetrafluoroethylene, friction powder, urushiol powder, rubber (ie, NBR, silicone, SBR, etc.).

[0054] In another embodiment of the present invention, the average friction material composition disclosed is as follows (% is by weight):

[0055]

[0056]

[0057] The invention finally also relates to a friction element, in particular a brake pad or a brake shoe, which exhibits a friction material layer made of the friction material composition described above.

[0058] The present invention also relates to a braking system comprising a component to be braked consisting of a brake disc or a brake drum made of cast iron or steel and at least one brake element consisting of a brake pad or a brake shoe, wherein the at least one brake element consisting of a brake pad or a brake shoe is designed to cooperate with the component to be braked through friction, wherein the brake component presents a friction layer intended to cooperate with the component to be braked and made of the above-mentioned friction material composition.

[0059] Exemplary Ways to Implement the Teachings of the Disclosure

[0060] The inventive and comparative examples are reported herein by way of illustration and are not intended to limit the present invention.

[0061] Example 1

[0062] Three formulations labeled "Dual Carbon 2%", "Dual Carbon 4%" and "Single Carbon" were prepared according to the following Table 1. The components shown in Table 1 are expressed as percentage values ​​by weight of the total weight of the composition.

[0063] The friction material compositions according to the present invention are represented by "dual carbon 2%" and "dual carbon 4%", and they differ based on the second carbonaceous material content.

[0064] The comparative friction material composition denoted as "monocarbon" has a standard NAO classification and is substantially the same as the composition of the present invention, but does not contain carbon having a D of less than 10 μm. 50 The composition of the second carbonaceous material.

[0065] Table 1

[0066] Components "Dual Carbon 2%" "Dual Carbon 4%" "Single Carbon" Abrasives with Mohs > 7 15-35 15-35 15-35 Abrasives with Mohs <7 30-60 30-60 26-56 Resin 6-10 6-10 6-10 Organic additives 4-8 4-8 4-8 Organic Fiber 2-4 2-4 2-4 Lubricants 2-8 2-8 2-8 <![CDATA[The first carbonaceous material (D 50 > 10 μm)]]> 2-6 2-6 2-6 <![CDATA[Second carbonaceous material (D 50 <10μm)]]> 2 4 total 100.00 100.00 100.00

[0067] The components shown in Table 1 are uniformly mixed in a horizontal mixer (e.g., a mixer of the Loedige type), and molded in a mold at a temperature of 160°C for 3 minutes under a pressure of 20 tons, and then cured at a temperature ranging from 150°C to 400°C for 10 minutes to 10 hours, thereby producing two friction materials according to the present invention, denoted as "Dual Carbon 2%" and "Dual Carbon 4%", and a comparative friction material denoted as "Single Carbon" for subsequent comparative testing; each friction material block thus obtained is made into an integral body with the same metal support comprising a flat steel plate (back plate) to form a vehicle brake pad.

[0068] Example 2: Wear, Particle Emission and Efficiency Testing

[0069] Each brake pad produced in the manner described in Example 1 was mounted on a brake caliper having a hydraulic actuator, which was then connected to a dynamometer and subjected to the following test.

[0070] The specifications of the dynamometer used are:

[0071] -DC motor 191kW,

[0072] -2000Nm constant torque up to 991rpm,

[0073] -Constant power from 911rpm to 200rpm,

[0074] - Braking torque 2000Nm,

[0075] -Maximum pressure: 200 bar,

[0076] -Maximum speed: 2600rpm,

[0077] - Mechanical inertia up to 50kg / m 2 ,

[0078] - Braking air intake / ventilation flow rate 1200m 3 / hour to 2000m 3 / Hour,

[0079] - 4 input analog channels for fixed temperature measurement,

[0080] - Friction level refinement.

[0081] Wear test

[0082] exist Figure 1 . The test results for a brake pad named "Dual Carbon 2%" comprising the friction material composition of the present invention and for a brake pad named "Single Carbon" comprising a comparative friction material composition are shown in FIG.

[0083] Specifically, Figure 1 The results depicted in the top part of relate to the thickness loss (in mm) of the inner and outer brake pads resulting from 1000 brake applications at 100° C., 200 brakes at 200° C., 500 brakes at 350° C., 500 brakes at 400° C. and 1000 brakes at 100° C. (repeating the first cycle). At the same time, the corresponding friction coefficient (μ) is shown.

[0084] Comparing the brake pad wear of the two test groups, it can be seen that the "Dual Carbon 2%" brake pad according to the invention shows the lowest thickness loss. This means that the "Dual Carbon 2%" brake pad has a longer life than the comparative "Single Carbon" brake pad and therefore it brings less wasted material (and therefore less environmental pollution) and maintenance costs.

[0085] It is worth noting that the friction coefficient of the "Dual Carbon 2%" brake pads is also more stable than that of the "Single Carbon" brake pads.

[0086] like Figure 1 As depicted on the bottom part of , with regard to the amount of mass loss (in grams), a determination is obtained that the wear of the "Dual Carbon 2%" brake pad is lower. In fact, the "Dual Carbon 2%" brake pad has the lowest mass loss compared to the "Single Carbon" brake pad.

[0087] It can be seen that with a D less than 10 μm 50 The presence of the second carbonaceous material included in the "Dual Carbon 2%" brake pad of the present invention acts on the heat generated during brake application, which, instead of accumulating in the brake pad and thereby destroying the adhesive, is dissipated.

[0088] Particle emission testing

[0089] The mass lost in the wear test is collected by suction on a test bench and subsequently analyzed in terms of particle number, amount of particulate matter (PM) and dispersion (given by the number of particles divided by the amount of PM). high resolution The instrument gives real-time particle number size distribution with up to 500 size classes ranging from 6 nm to 10 μm.

[0090] PM and PN were measured during the AKM test.

[0091] pass eFilter TM The amount of PM (in grams) is obtained by an instrument that combines a standard gravity filter holder with sensitive real-time PM detection.

[0092] The particle emission test results are reported in Table 2.

[0093] Table 2

[0094] "Dual Carbon 2%" "Single Carbon" Number of particles (#) <![CDATA[3,9x10 13 ]]> <![CDATA[6,7x10 13 ]]> Particulate matter (mg) 5,2 <![CDATA[1,0x10 1 ]]> Dispersion ratio (# / mg) <![CDATA[4,2x10 12 ]]> <![CDATA[6,4x10 12 ]]>

[0095] It is noteworthy that the lost mass of the "Dual Carbon 2%" brake pad contains a lower number of harmful particles, ranging from ultrafine particles of nanometer size to coarse particles with a diameter of 10μm, compared to the lost mass emitted by the comparative "Single Carbon" brake pad. At the same time, the amount of particulate matter emitted by the "Dual Carbon 2%" brake pad during the braking test is lower than the amount of particulate matter emitted by the comparative "Single Carbon" brake pad.

[0096] Efficiency test

[0097] The efficiency test is carried out according to the AK-Master standard.

[0098] Figure 2 and Figure 3 A typical report showing the results obtained according to the AK-Master standard, presenting the "single carbon" ( Figure 2 ) and "Dual Carbon 2%" ( Figure 3 )The different steps and cycles of a brake pad and key variables such as friction (μ), pressure and temperature are shown.

[0099] Specifically refer to the decay part of step 9 of the AK-Master standard test, which consists of 15 consecutive braking actions with fixed deceleration, initial velocity and final velocity. Specifically,

[0100] -Deceleration constant: 4m / s 2 ,

[0101] - Initial speed: 100km / h,

[0102] - Final speed: 5km / h,

[0103] - Minimum temperature to be reached at the end of the test: 550°C.

[0104] Of particular importance is the comparison with "monocarbon" brake pads ( Figure 2 ) and the present invention's "dual carbon 2%" brake pad ( Figure 3 ) The "Dual Carbon 2%" brake pad according to the present invention exhibits an overall nominal friction level comparable to the comparative "Single Carbon" brake pad; however, the fade performance of the "Dual Carbon 2%" brake pad is slightly more stable along all fade portions than the fade performance of the comparative "Single Carbon" brake pad.

[0105] Example 3: Evaluation of creeping chatter noise using a lab-scale tribometer

[0106] The tribometer used to test creep chatter noise is equipped with a climate chamber for humidity evaluation and has the following specifications:

[0107] - Rotor speed: 0,1rpm to 5000rpm

[0108] - Torque: 0,01Nm to 5Nm

[0109] -Maximum load capacity: 2000N.

[0110] The tribometer samples were made of 10 mm x 10 mm of the friction material under investigation and a cast iron disc. For each friction material, a new disc was used for the measurement at the tribometer.

[0111] Figure 4 The variation of the coefficient of friction of three friction materials ("Single Carbon", "Dual Carbon 2%" and "Dual Carbon 4%) subjected to a normal force of 200 N at a disc rotation of 2 rpm as a function of time is shown for several relative humidities (20% RH, 40% RH, 60% RH, 80% RH and 90% RH). Each test was repeated three times (braking 1, braking 2 and braking 3).

[0112] Based on the non-resonant vibration of the friction coefficient defining the so-called "discontinuous creep flutter" area (i.e., the area circled in the rectangle of the figure), the number of stick-slip phenomena and the stick-slip amplitude for each test can be calculated. Specifically, the stick-slip amplitude is calculated as the average value of the difference between the static friction coefficient and the dynamic friction coefficient.

[0113] Figure 4 The stick-slip amplitude and stick-slip number according to humidity for three friction materials are shown. The stick-slip amplitude and stick-slip number are generated by the sum of three tests (brake 1, brake 2 and brake 3), and the error is the standard deviation of the three times.

[0114] It is noteworthy that the “Dual Carbon 4%” friction material, followed by the “Dual Carbon 2%” friction material, reduced the occurrence of stick-slip in terms of both magnitude and frequency relative to the comparative “Single Carbon” brake pad.

[0115] It is therefore clear that the "Dual Carbon 4%" and "Dual Carbon 2%" brake pads according to the invention have a significantly lower tendency to creep shudder noise than the comparative "Single Carbon" brake pads.

[0116] Example 4: Porosity of the friction material according to the present invention

[0117] Mercury porosimetry was used to characterize the porosity of the three friction materials studied in terms of open porosity, pore size and their distribution.

[0118] The results are shown in Figure 5 and are summarized in Table 3.

[0119] Table 3

[0120] "Dual Carbon 2%" "Dual Carbon 4%" "Single Carbon" Open porosity [%] 18 15 20 Median pore size (μm) 0,3205 0,1752 0,4067

[0121] It is noteworthy that the porosity of the "Dual Carbon 4%" friction material according to the present invention, and secondarily the porosity of the "Dual Carbon 2%" friction material, is lower than the porosity of the comparative "Single Carbon" friction material.

[0122] The same trend also applies to the average pore size. In fact, according to the present invention, the "Dual Carbon 4%" friction material has the smallest average pore size, followed by the "Dual Carbon 2%" friction material.

[0123] Therefore, it is clear that the ultrafine second carbonaceous material present only in the friction material according to the present invention unexpectedly contributes to reducing the porosity of the friction material.

[0124] Due to the lower porosity, the friction material according to the invention turns out to be less sensitive to relative humidity and the stick-slip phenomenon is therefore less negatively influenced by humidity.

[0125] At the same time, the smaller average pore size of the friction material according to the present invention results in better adhesion between the friction material surface and the disc surface, thereby further reducing the occurrence of stick-slip behavior.

[0126] From the above working examples and disclosure, it is clear that the friction material compositions prepared according to the present disclosure have low propensity for creeping chatter noise due to reduced stick-slip phenomena; low particle emissions directly related to reduced material wear, and improved friction stability relative to comparative compositions.

[0127] Therefore, all objects of the present disclosure are achieved.

[0128] Certain terms

[0129] Although certain braking devices, systems and methods have been disclosed in the context of certain exemplary embodiments, it will be understood by those skilled in the art that the scope of the present disclosure extends the specifically disclosed embodiments to other alternative embodiments and / or uses of the embodiments and certain modifications and equivalents thereof, such as brake displays for brake drum-based braking systems. Use with any structure is clearly within the scope of the present invention. Various features and aspects of the disclosed embodiments may be combined or substituted with each other to form different modes of assembly. The scope of the present disclosure should not be limited by the specific disclosed embodiments described herein.

[0130] Conditional language such as "may," "might," "might," or "might," unless specifically stated otherwise or otherwise understood in the context in which it is used, is generally intended to convey that certain embodiments include or do not include certain features, elements, and / or steps. Thus, such conditional language is generally not intended to imply that one or more embodiments require a feature, element, and / or step in any way.

[0131] Unless otherwise indicated, the terms "approximately", "about" and "substantially" as used herein refer to an amount that is close to the amount and still performs the desired function or achieves the desired result. For example, in some embodiments, the terms "approximately", "about" and "substantially" may refer to an amount that is less than or equal to 10% of the amount, depending on the context. Similarly, the term "generally" as used herein refers to a value, amount or feature that mainly includes or tends to a specific value, amount or feature.

[0132] The present disclosure explicitly contemplates that the various features and aspects of the disclosed embodiments can be combined or replaced with each other. Therefore, the scope of the present disclosure should not be limited by the above-mentioned specific disclosed embodiments, but should only be determined by a reasonable interpretation of the full scope of the attached claims and their equivalents.

Claims

1. An asbestos-free friction material composition, comprising: at least one filler; at least one fiber material selected from inorganic fibers, organic fibers, metal fibers and any combination thereof; at least one binder; at least one lubricant; at least one or more abrasives; at least a first carbonaceous material and at least a second carbonaceous material, It is characterized in that Combination: The first carbonaceous material has a D greater than 10 μm 50 The particle size distribution, and The second carbonaceous material has a D smaller than 10 μm. 50 of particle size distribution.

2. The asbestos-free friction material composition according to claim 1, characterized in that: With D greater than 10 μm 50 The at least first carbonaceous material is present in the friction material composition in an amount ranging from 2 wt % to 6 wt % based on the total weight of the friction material composition.

3. The asbestos-free friction material composition according to claim 1 or 2, characterized in that: With a D less than 10 μm 50 The at least second carbonaceous material is present in the friction material composition in an amount ranging from 1 wt % to 4 wt % based on the total weight of the friction material composition.

4. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The composition ratio between the first carbonaceous material and the second carbonaceous material ranges from 1:1 to 6:1, and preferably from 2:1 to 3:

1.

5. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that With D greater than 10 μm 50 The at least first carbonaceous material is selected from graphite, petroleum coke, dried petroleum coke, carbon black and any mixture thereof.

6. The asbestos-free friction material composition according to claim 5, characterized in that: With D greater than 10 μm 50 The at least first carbonaceous material is graphite.

7. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that With a D less than 10 μm 50 The at least second carbonaceous material is selected from fillers including carbon black.

8. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The at least one fiber material comprises: organic fibers selected from the group consisting of polyacrylic fibers, polyaramid fibers, aromatic polyamide fibers, cellulose fibers, any mixture thereof; and / or inorganic fibers or metal fibers.

9. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The at least one lubricant consists of a sulfide-based lubricant selected from the group consisting of metal sulfides of Sn, Zn, Fe, Mo and mixtures thereof.

10. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The at least one or more abrasives include at least one soft abrasive having a Mohs hardness of less than 7 and selected from magnesium oxide, chromite, magnetite, hematite, quartz, zinc oxide, tin oxide, barium sulfate, silicates, fluorides, and any mixtures thereof.

11. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The at least one or more abrasives include at least one hard abrasive having a Mohs hardness greater than 7 and preferably having a slightly rounded shape, the hard abrasive being selected from zirconium oxide, aluminum oxide, corundum, silicon carbide, tungsten carbide, zirconium carbide, zirconium silicate, boron nitride and any mixture thereof.

12. The asbestos-free friction material composition according to claims 10 to 11, characterized in that: The composition ratio between the soft abrasive and the hard abrasive is in the range of 1:1 to 4:

1.

13. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The asbestos-free friction material composition does not contain copper and does not contain any copper alloys.

14. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The asbestos-free friction material composition comprises at least one metal other than copper and copper alloys, wherein the at least one metal other than copper and copper alloys is selected from iron, steel, stainless steel, tin, zinc and any alloys thereof in the form of powder or fiber.

15. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The at least one filler is an inorganic filler selected from the group consisting of mineral fiber, glass fiber, rock wool, layered silicate (mica, vermiculite, talc), titanate, inorganic hydroxides of Ca, Mg, K and any mixture thereof.

16. The asbestos-free friction material composition according to any one of the preceding claims, characterized in that The asbestos-free friction material composition comprises the following components in weight percentage based on the total weight of the friction material composition:

17. A friction element having a friction layer made of the friction material composition according to any one of the preceding claims.

18. The friction element according to claim 17, characterized in that The friction element is a brake pad or a brake shoe.

19. A braking system comprising a member to be braked consisting of a brake disc or brake drum made of cast iron or steel and at least one braking member consisting of a brake pad or brake shoe, the at least one braking member consisting of a brake pad or brake shoe being suitable for cooperating with the member to be braked by friction, characterized in that: The brake member has a friction layer made of the friction material composition according to claims 1 to 16, which is intended to cooperate with the member to be braked.

Citation Information

Patent Citations

  • Non-asbestos disc brake pad for automobiles

    EP0959262A1

  • Hybrid friction lining material, brake linings produced from same and method for producing same

    WO2019120648A1